Effects of Dextroamphetamine on Cognitive Performance and Cortical Activation - Mattay, Venkata S.; Callicott, Joseph H.; Bertolino, Alessandro; Heaton, Ian; Frank, Joseph A.; Coppola, Richard; Berman, Karen F.; Goldberg, Terry E.; Weinberger, Daniel R. (NeuroImage (Orlando, Fla.), 2000)
Monoaminergic neurotransmitters are known to have modulatory effects on cognition and on neurophysiological function in the cortex. The current study was performed with BOLD fMRI to examine physiological correlates of the effects of dextroamphetamine on working-memory performance in healthy controls. In a group analysis dextroamphetamine increased BOLD signal in the right prefrontal cortex during a task with increasing working-memory load that approached working-memory capacity. However, the effect of dextroamphetamine on performance and on signal change varied across individuals. Dextroamphetamine improved performance only in those subjects who had relatively low working-memory capacity at baseline, whereas in the subjects who had high working-memory capacity at baseline, it worsened performance. In subjects whose performance deteriorated, signal change was greater than that in subjects who had an improvement in performance, and these variations were correlated (Spearman ρ = 0.89, P < 0.02). These data shed light on the manner in which monoaminergic tone, working memory, and prefrontal function interact and, moreover, demonstrate that even in normal subjects the behavioral and neurophysiologic effects of dextroamphetamine are not homogeneous. These heterogeneic effects of dextroamphetamine may be explained by genetic variations that interact with the effects of dextroamphetamine.